Methods of Maintaining Dental and Oral Hygiene During Fixed Orthodontic Wear - Nur, Arnela; Liana, Intan; Lismanidar, Lismanidar (Journal Dental Health, 2023)
The development of partnerships involving the entire healthcare sector, including healthcare professionals tasked with general health and oral health specifically. This research includes literature studies by seeking relevant theoretical references on the encountered cases or issues. Knowledge will influence behavior, and behavior will prompt actions based on individual knowledge. The use of orthodontia is indeed useful for aligning teeth, but for fashion orthodontia users, it is recommended to undergo self-care and regular check-ups to prevent any unwanted anomalies.